Pemikiran Hukum Progresif untuk Perlindungan Hukum dan Kesejahteraan Masyarakat Hukum Adat - Muh. Afdal Yanuar (The Constitutional Court of the Republic of Indonesia, 2021)
Today there are still many problems with the existence and traditional rights of indigenous and tribal peoples. These problems tend to place the indigenous and tribal peoples in a weak and marginalized position. Not without reason, it is due to the unequal perception of all related parties, in positioning customary land and indigenious peoples in the context of national and state life based on Pancasila and the Constitution. The issue that will be discussed in this paper is about how to realize progressive legal protection of the existence of indigenous and tribal peoples to realize their welfare. This paper will use the conceptual approach method, namely the Pancasila concept as a source of ideas in providing legal protection to indigenous and tribal peoples. Furthermore, it also uses a conceptual approach from thought of progressive law. The existence of the status quo in providing legal protection to indigenous and tribal peoples which tends to be static, conditional and legalistic which has been done so far. Legal protection is more concerned with how the criteria regarding indigenous and tribal peoples will be recognized. The state should have dared to make policy and legal breakthroughs to provide legal protection based on guidance and empowerment. These policy and legal breakthroughs can refer to thougt of progressive law, which positions the law for humans with the aim of providing justice, welfare and happiness for indigenous and tribal peoples based on Pancasila and the Constitution.